The Role of Social Capital in Enhancing Parental Participation in Children's Education in Primary Schools - Hendri Saputra (LP3M KH Yazid Karimullah Institute, 2025)
Parental involvement in children's education is an important factor in improving children's learning outcomes and character development. This study aims to analyze the role of social capital in shaping active parental participation in elementary school environments. This research approach is qualitative with a case study method in three elementary schools in Yogyakarta and Padang. Data were obtained through in-depth interviews with teachers, parents, and principals, as well as observations of school activities. The results showed that social capital, such as trust between school members, social networks between parents, and shared norms, contributed significantly to encouraging parental involvement. Schools that succeeded in building open and collaborative communication showed an increase in parental attendance at school meetings, involvement in home learning activities, and support for extracurricular activities. This study concluded that strengthening social capital in the school environment can be an effective strategy in improving the quality of elementary education through community participation.